Directed Technical Change and Capital Deepening: A Reconsideration of Kaldor's Technical Progress Function - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
This note proposes a growth model that is derived from the standard Solow growth model by replacing the neoclassical production function with Kaldor's technical progress function while maintaining a marginalist theory of factor prices in the spirit suggested by von Weizsäcker (1966, 1966b). The hybrid model so obtained accounts for balanced growth in a way that appears less arbitrary than the Solow model, especially because it directly accounts for Harrod neutral technical change, without any need for further assumptions.
urn:nbn:de:bvb:19-epub-20959-4
Keywords: O30; O40; E12; E13; E25; B59; B31; 330; directed technical change; directed technological change; bias in innovation; technical progress function; neoclassical production function; Harrod neutrality; Hicks neutrality; Cambridge theory of distribution; marginal productivity theory; Kaldor; Kennedy; von Weizsäcker; Solow model